Autism spectrum disorder identification in schools: Impact of criteria, assessments, and student data for identification decisions. Issue 4 (12th February 2022) - Duesenberg, McKinzie D.; Burns, Matthew K.
Abstract: Autism spectrum disorder (ASD) is often diagnosed by clinical practitioners with criteria from the American Psychiatric Association, but an educational diagnosis is usually based on state special education law and is geared towards addressing concerns within schools. The current study aims to examine the extent to which the clinical diagnosis of ASD corresponds to the educational diagnosis of Autism, and what factors and assessments influenced the diagnosis. Data consisted of 32 randomly selected deidentified initial school evaluation reports (autism = 16; non‐autism = 16) from one midwestern state. The reports were coded based on identification methods and student data. Results indicate that the Autism Diagnostic Observation Schedule, Second Edition assessment was the strongest predictor of Autism eligibility within schools, but students with a cognitive ability score that was one standard deviation below the mean (i.e., standard score £84) were more frequently identified with educational eligibility of ASD (AU) by a factor of 14.67 as compared with individuals with a higher cognitive score. Implications for future research and practice are included. Key Points/Highlights: Autism assessment score, cognitive score, grade, and previous educational qualification affect autism (AU) identification in schools. There is a need for formalized assessment procedures and protocols for AU in schools.